PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA PADA KOMITE OLAHRAGA NASIONAL INDONESIA (KONI) KOTA YOGYAKARTA - tegar alifahmi ginting (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to analyze the influence of organizational culture on work performance, motivation influence on job performance, job satisfaction influence on work performance, and organizational culture influence, motivation, and job satisfaction simultaneously on work performance at employees of Komite Olahraga Nasional Indonesia (KONI) Yogyakarta. Variables are Organizational Culture X1, Motivation X2, Job Satisfaction X3 and Job Performance Y.Populasi in this research is employees of Komite Olahraga Nasional Indonesia (KONI) Yogyakarta.Sampel sample is 42 employees, with sample technique used is census sampling. Methods of data collection using questionnaire method, data analysis using multiple regression. Result of research with 5% or 0,05 significance level indicates that organizational culture has a significant positive effect on work performance (0,000 <0,05) Motifation has no significant effect on employee performance which is indicated by significance value (0,344> 0,05) and job satisfaction have a significant effect on work performance (0.000 <0,05). Simultaneously variable of organizational culture, motivation, and job satisfaction have an effect on signifikan to work performance of Komite Olahraga Nasional Indonesia (KONI) Yogyakarta.